Comparison of plate and screw constructs versus screws only for anterior distal femoral hemiepiphysiodesis in children. Issue 1 (January 2020) - Nazareth, Alexander; Gyorfi, Michael J.; Rethlefsen, Susan A.; Wiseley, Benjamin; Noonan, Kenneth; Kay, Robert M.
Abstract : The study aim was to compare methods of anterior distal femoral hemiepiphysiodesis (ADFH) for treatment of fixed knee flexion deformities in ambulatory children with neuromuscular conditions and flexed knee gait. This is a retrospective review of 47 children (14 female, 33 male, age at surgery: 12.1 ± 2.7 years) who underwent ADFH between 2009 and 2016. Subjects were grouped by ADFH construct: one transphyseal screw (N = 11), two transphyseal screws (N = 28) or plates and screws (P/S group, N = 8). Clinical/radiographic variables were analyzed using paired t tests, χ 2 tests, multiple regression and analysis of covariance. Participants experienced significant reduction in knee flexion contractures (Δ12°, P < 0.006), with no difference among groups ( P = 0.43). Postoperative knee pain was significantly more prevalent in the P/S group (5/8, 63%) than the 1-SCR group (0/11, 0%) and the 2-SCR group (2/28, 7%) ( P = 0.002). ADFH results in significant reduction of knee flexion deformity and improved knee extension during gait. Plate and screw constructs, the 1 and 2 transphyseal screw techniques are equally effective, but plate and screw constructs may be associated with a higher risk of persistent postoperative knee pain.